Reevaluating Backup Monitor Chamber Tolerances for Stereotactic Body Radiotherapy Treatments using Volumetric-modulated Arc Therapy - Yong Sang; Jun Dang; Jianan Wu; Enzhuo Quan (Journal of Medical Physics)
Background: Backup monitor chambers in medical linear accelerators play a critical role by verifying the radiation dose delivery and providing a failsafe mechanism to terminate the beam if dose discrepancies are detected. The American Association of Physicists in Medicine’s Task Group 142 recommends a 2% constancy tolerance for these chambers, which is suitable for conventional radiotherapy but may not be adequate for stereotactic body radiotherapy (SBRT) due to its high monitor units (MUs) per fraction. This study evaluates the backup monitor chamber constancy in SBRT treatments using volumetric-modulated arc therapy (VMAT) on the Elekta Infinity accelerator to determine if the current tolerances ensure treatment efficacy and safety. Methods: Five SBRT patients treated with VMAT on the Elekta Infinity accelerator between January 2024 and June 2024 were retrospectively selected for this study. The patients’ treatment plans involved tumors in various locations, including the liver, lungs, spine, and brain. Each plan was executed in quality assurance mode, and the deviations between the primary (MU1) and backup (MU2) MUs were recorded at five different tolerance levels: 1.5%, 1.0%, 0.5%, 0.0%, and − 1.5%. In this study, “tolerance” refers to the allowable percentage deviation between MU1 and MU2 readings. A positive tolerance allows MU2 to exceed MU1 by the specified percentage, while a negative tolerance allows MU2 to be lower than MU1 by the specified percentage. A tolerance of 0% requires MU1 and MU2 to match exactly. The study also assessed the impact of gantry angle and field size on MU2 readings, with gantry angles ranging from 0° to 180° and field sizes from 2 cm × 2 cm to 30 cm × 30 cm. Data on any treatment errors and beam interruptions caused by MU2-MU1 deviations were analyzed. Results: At the 1.5% tolerance setting, all five SBRT plans experienced at least one delivery error, with MU2 exceeding MU1 by more than 10 MUs. Reducing the tolerance to 1.0% decreased the number of errors, but high-MU arcs still triggered errors. At a 0.5% tolerance, errors persisted in high-MU cases such as multi-target lung cancer. However, at the 0.0% and −1.5% tolerance settings, no errors were reported. In addition, minor variations in gantry angles (up to 0.2%) slightly affected MU2 readings, while field size had no significant impact. Conclusions: The current 2% constancy tolerance may not be optimal for SBRT treatments on the Elekta Infinity accelerator. We recommend a tolerance as close to 0.0% as possible to minimize the delivery errors and ensure patient safety. Further research is needed to validate these findings across different accelerator models and patient populations.